2017
DOI: 10.1038/s41598-017-00043-9
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes for gene expression studies in the mouse heart

Abstract: To be accurate, quantitative Polymerase Chain Reaction (qPCR) studies require a set of stable reference genes for normalization. This is especially critical in cardiac research because of the diversity of the clinical and experimental conditions in the field. We analyzed the stability of previously described as potential reference genes in different subsets of cardiac tissues, each representing a different field in cardiac research. The qPCR dataset was based on 119 different tissue samples derived from cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…On the other hand, our analysis has revealed that the expression pattern of the actin gene (Actb), often considered as a reliable reference gene in other studies 32 , steadily decreased throughout the reprogramming. As a result, this gene was consistently ranked as one of the most unstable genes across different statistical methods.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, our analysis has revealed that the expression pattern of the actin gene (Actb), often considered as a reliable reference gene in other studies 32 , steadily decreased throughout the reprogramming. As a result, this gene was consistently ranked as one of the most unstable genes across different statistical methods.…”
Section: Discussionmentioning
confidence: 78%
“…30 The expression patterns of control genes are presented in Supplemental Figure S3B. Expression of Actb, Rpl4, Rpl32, Tbp, Oaz1 and Pgk1 did not change significantly, whereas several other genes either generally used or recommended as control genes 31 , such as Gapdh, were up-or downregulated (q < 0.01 and fold change > 1.5) in at least one time-point comparison. Differential expression analysis of all protein-coding genes is available in Supplemental Dataset S1.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…qRT-PCR was performed using SYBR Green (Roche) on a Lightcycler 480 system II (Roche). In case of multi-tissue qPCRs, the geometric mean of multiple reference genes was used [ 32 ]. Analysis of qRT-PCR data was done using LinRegPCR analysis software [ 33 ].…”
Section: Methodsmentioning
confidence: 99%